Comparison of transabdominal and transvaginal ultrasound in the diagnosis of uterine scar failure - Jumabaeva Elmira Kuanishbaevna (Genius Journals, 2025)
The rate of cesarean sections continues to rise worldwide, leading to an increase in the number of pregnant women with uterine scars. One of the most dangerous complications in this category of women is scar failure, which can lead to uterine rupture during pregnancy and childbirth. Ultrasound is the primary method for assessing scar condition, but the optimal approach—transabdominal or transvaginal—remains a matter of debate. In recent years, there has been a steady increase in the number of cesarean sections, which naturally leads to an increase in the proportion of pregnant women with uterine scars. According to WHO data (2021), the cesarean section rate in some countries reaches 25–30%, and this figure is expected to continue to increase. Against this backdrop, the development of optimal methods for diagnosing scar integrity is increasingly important, as scar leakage is a high-risk factor for uterine rupture and perinatal and maternal complications (Silver R.M., 2019; Sentilhes L., 2020). At the same time, transvaginal ultrasound in our study demonstrated significantly higher information yield. It allowed us to accurately determine the thickness of the lower uterine segment in the scar area, assess the shape of the internal contour, and identify minor defects. Specifically, it has been shown that a scar thickness of less than 2.5 mm, detected transvaginally, is associated with a high risk of uterine rupture during childbirth (Bujold E., 2017).
Keywords: uterine scar; cesarean section; scar integrity